(untitled) (Archive of Conferences, 2021)
The article is devoted to the movement of the mixture of cotton and air in two branches. The purpose is to direct the high air, cotton to the canal. When a canal splits into two branches, the flow can be reversed, and the formation of clumps can have negative consequences. Replacing the boundary of the circle with a smooth curved arc relative to the flow is required to determine its shape and radius of curvature. The problem was solved using the theory of ideal fluids. Necessary formulas, numerical results have been obtained and can be used to improve the pneumo-separator.